Cyanide containing reagent use for gold leaching of oxidated gold containing ores - A Z Issagulov; A K Tursunbaeva; D G Akimbaeva; V S Portnov (RUDN Journal of Engineering Research, 2008)
There is a basic opportunity of use of cyanide containing reagent, received from wastes of phosphoric industry, for gold leaching of oxidated gold containing ores.